Effects of Grinding Corn with Different Moisture Concentrations on Subsequent Particle Size and Flowability Characteristics - M. B. Braun; K. M. Dunmire; C. E. Evans; C. R. Stark; C. B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2019)
The objective of this study was to determine the effects of whole corn moisture and hammermill screen size on subsequent ground corn moisture, particle size, and flow- ability. Whole yellow dent #2 corn was used for this experiment. Treatments were arranged as a 2 × 2 factorial design with two moisture concentrations (as-received and high) each ground using 2 hammermill screen sizes (1/8 and 1/4 in). Corn was ground using a laboratory scale 1.5 HP Bliss Hammermill (Model 6K630B) at 3 separate time points to create 3 replications per treatment. Increasing initial whole corn moisture was accomplished by adding 5% water and heating at 55°C for 3 hours in sealed glass jars using a Fisherbrand Isotemp Oven (Model 15-103-051). Ground corn flowability was calculated using angle of repose (AOR), percent compressibility, and critical orifice diameter (COD) measurements to determine the composite flow index (CFI). There was no evidence for a screen size × corn moisture interaction for moisture content, particle size, standard deviation, or flowability metrics. Grinding corn using a 1/8 in screen resulted in decreased (P<0.041) moisture content compared to corn ground using the 1/4 in screen. There was a decrease in particle size from the 1/4 in screen to the 1/8 in but no evidence of difference was observed for the standard deviation. There was a decrease (P<0.03) in percent compressibility as screen size increased from 1/8 to 1/4 in. Angle of repose tended to decrease (P<0 .056) when corn was ground using a 1/4 in screen compared to a 1/8 in screen. For the main effects of moisture content, high moisture corn had increased (P<0.0001) ground corn moisture content compared to as-received corn. As-received corn resulted in decreased (P<0.029) particle size and an increased standard deviation compared to the high moisture corn. Increased moisture content of corn increased (P<0.038) CFI and tended to decrease (P<0.056) AOR and COD. In conclusion, decreasing hammermill screen size increased moisture loss by 0.55%, corn particle size by 126 μm, and resulted in poorer flowability as measured by percent compressibility and AOR. High moisture corn increased subsequent particle size by 89 μm, therefore improving flowability as measured by CFI.
Keywords: corn; grind; moisture; flowability; particle size